ACR Appropriateness Criteria Right Upper Quadrant Pain - Yarmish, Gail M. (J Am Coll Radiol, 2014)
Acute right upper quadrant pain is a common presenting symptom in patients with acute cholecystitis. When acute cholecystitis is suspected in patients with right upper quadrant pain, in most clinical scenarios, the initial imaging modality of choice is ultrasound. Although cholescintigraphy has been shown to have slightly higher sensitivity and specificity for diagnosis, ultrasound is preferred as the initial study for a variety of reasons, including greater availability, shorter examination time, lack of ionizing radiation, morphologic evaluation, confirmation of the presence or absence of gallstones, evaluation of bile ducts, and identification or exclusion of alternative diagnoses. CT or MRI may be helpful in equivocal cases and may identify complications of acute cholecystitis. When ultrasound findings are inconclusive, MRI is the preferred imaging test in pregnant patients who present with right upper quadrant pain. The ACR Appropriateness Criteria are evidence-based guidelines for specific clinical conditions that are reviewed every 2 years by a multidisciplinary expert panel. The guideline development and review include an extensive analysis of current medical literature from peer-reviewed journals and the application of a well-established consensus methodology (modified Delphi) to rate the appropriateness of imaging and treatment procedures by the panel. In those instances in which evidence is lacking or not definitive, expert opinion may be used to recommend imaging or treatment.